Rediscovering the Child: Review of Montessori Educator Research Projects 2023 –2024 - Gerker, Heather (Journal of Montessori Research, 2024)
Maria Montessori’s early emphasis on systematic observation and experimentation to understand children’s learning predates the formal recognition of the “teacher as researcher” role, which emerged in the 1950s. This article explores the use of action research today in Montessori education, focusing on classroom-based action research (CBAR) and practitioner inquiry as key methodologies for enhancing teaching practices. We begin by defining classroom-based action research and its application in Montessori teacher education, highlighting its role in fostering reflective, evidence-based investigations that improve classroom practices. Two CBAR studies from the University of Wisconsin-River Falls are presented: (1) Kaul’s exploration of student choice in math practice and (2) Thompson’s investigation of structured literacy in a Montessori Children’s House. The article also discusses practitioner inquiry projects from Loyola University Maryland, which examine the inclusion of students with attention deficit-hyperactivity disorder (ADHD) and the effectiveness of Montessori Math materials in promoting math fluency.